Effect of morphology-induced interfacial defects on band location and enhanced photocatalytic dye degradation activity of TiO2/Graphene aerogel. (March 2022) - Wang, Yaoyao; Li, Liyuan; Lu, Haimei; Wang, Chao; Zhao, Yang; Kuga, Shigenori; Huang, Yong; Wu, Min
Abstract: Two different morphologies of TiO2, namely nanorods (NRs) and ultrathin nanowires (uNWs), have been grown on graphene aerogel (GA), denoted as TiO2 NR@GA and TiO2 uNW@GA, to investigate the variation of band-gap structure and the generation of multiple intermediate energy levels caused by heterogeneous interfaces. In comparison to TiO2 NRs and nanowires (NWs), TiO2 in both composites shows a much smaller size or diameter due to the graphene-confined growth during the hydrothermal process. The positions of band edges and the distributions of defect energy levels have been measured and calculated. The band gap of TiO2 in TiO2 uNW@GA is more extensively modified than that in TiO2 NR@GA as a result of the ultrathin (8–10 nm) diameter of TiO2 NWs, a larger interfacial region, and blurred boundaries between interfacial defects and bulk defects. The dramatically modified band gap facilitates the separation and transmission of photoinduced electrons and holes. Thus, TiO2 uNW@GA with a bicrystalline phase (anatase:bronze, 1:3) exhibits higher photocatalytic activity than anatase TiO2 NR@GA. This study establishes a foundation for improving photocatalytic performance by engineering interfacial defects of graphene-based metal oxides. Graphical abstract: Image 1 Highlights: Increased defective interfacial areas have been achieved by graphene-confined in situ growth of TiO2 nanorods and nanowires. The dramatically modified band gap facilitates the separation and transmission of photoinduced electrons and holes. Graphene-supported TiO2 ultrathin nanowires with a bicrystalline phase exhibit higher photocatalytic activity than graphene-supported anatase TiO2 nanorods.